Personalism, sexualism and dissolution in postmodernism: A critique of liberal conception of rights - Segovia, Juan Fernando (Derecho Público Iberoamericano, 2012)
The purpose of the work is to consider the relationship between personalism and postmodernity, and the concepts of law and rights this association originate. The author does not assume that personalism does not resist the dissolution of the self of the postmodern deconstructionism wave. He asserts that personalism and postmodernity are plainly compatible and they have a mutual influence in the new liberal and sexualized human rights generation.